Increasing the motivation of madrasah Aliyah students to learn cross-interest English subject by applying the game “relay race” - Annafiah, Afiya Ulin Nuha (English Learning Innovation, 2024)
Cross-interest subjects are programs and policies from the government that aim to provide opportunities for students to choose and study subjects that are not in the specialization program so that they will add insight, experience, and knowledge that they have later. In theory, students should have a high motivation or enthusiasm for learning to study the cross-interest subjects they have chosen. However, the facts in the classroom show the opposite. This study aims to increase student learning motivation in English Cross Interest subjects in class XI MIPA Madrasah Aliyah Negeri Kota Batu through the application of a "relay race" or relay game. This research is a class action research with the research subject of XI MIPA 2 class with 36 students. The research was conducted with two cycles on simple past-tense material. Data collection techniques were carried out by observation through daily notes filled by both the teacher and students, and questionnaires filled by students to determine the level of student learning motivation. The results showed increased student learning motivation in cross-interest English subjects, with an average percentage in the first cycle of 81% and increased by 1% to 82% in the second cycle. Thus, it can be concluded that applying the "relay race" game can increase students' learning motivation while still paying attention to the teacher’s pedagogical skills during the learning process.